Sur l’histoire du quotidien et la religion - Hubert, Ollivier (Études d'histoire religieuse, 2007)
Recounting the history of everyday life in its various forms poses different problems in regard to the time period under examination and the scholarly approach being taken. While French "histoire des mentalités" remained on the level of the abstract, other schools - Italian, German and British - returned the emphasis to the individual, the ordinary citizen confronted by the many trivial necessities of everyday life. The telling of Quebec's religious history became part of this social historical trend. Exploring archives which evoked the ordinary life of the parishes, these historians described a concrete religion, inseparable from forms of local sociability. Another kind of history of everyday life is possible, however: one that seeks not to make sense of ordinary events, but to produce a history of the category itself, and of its incorporation. It involves, in fact, a renewed emphasis on structure and its evolution, a history of defined time, represented and experienced through repetition. Taken from this perspective, religious history has much from which to benefit.